Ties That Bind: How Business Connections Affect Mutual Fund Activism. (December 2016) - CVIJANOVIĆ, DRAGANA; DASGUPTA, AMIL; ZACHARIADIS, KONSTANTINOS E.
ABSTRACT: We investigate whether business ties with portfolio firms influence mutual funds' proxy voting using a comprehensive data set spanning 2003 to 2011. In contrast to prior literature, we find that business ties significantly influence promanagement voting at the level of individual pairs of fund families and firms after controlling for Institutional Shareholder Services (ISS) recommendations and holdings. The association is significant only for shareholder‐sponsored proposals and stronger for those that pass or fail by relatively narrow margins. Our findings are consistent with a demand‐driven model of biased voting in which company managers use existing business ties with funds to influence how they vote.